Modeling and Simulation of a Solar Photovoltaic System, Its Dynamics and Transient Characteristics in LABVIEW - Musa Abdulkadir; A. S. Samosir; A. H. M. Yatim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
This paper proposes a LABVIEW simulator for photovoltaic (PV) systems. The effect of irradiance and temperature on PV module is very crucial when computing the model PV parameters. Many modeling techniques were used but this approach enables the computation of model parameters at any irradiance and temperature point. It has the ability to simultaneously compute all the PV model parameters. The accuracy of the simulator is verified by applying the model to 36 W PV modules. The performance of the model is tested using a single diode model, a shunt resistance Rp and series resistance Rs. The proposed model was found to be better and accurate for any irradiance and temperature variations. The proposed model can be very useful for PV Engineers and expert who require a simple, fast and accurate PV simulator to design their systems.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.2422